Inštitucionálna starostlivosť o zdravie seniora = Institutional health care for the elderly - Orieščiková, Helena (Vilnius: Mykolas Romeris Universitetas)
Elderly care is considered as team, multidisciplinary and multi-agency care nowdays and it is an issue for society as a whole. Its target is to ensure as much as possible the health of seniors and their ability to live quality and independent life as long as possible in their regular environment.
Keywords: seniorzy; opieka zdrowotna; opieka społeczna; starość; seniors; health care; social care; old age